Flood injustice in 500-year floodplains - Farshid, Ali; Null, Sarah E. (Frontiers in Human Dynamics, 2025)
Urban flooding presents a global challenge, disproportionately affecting socially vulnerable communities. In the U.S., catastrophic floods are compounded by climate change, aging infrastructure, rapid land development, and population growth. Flooding causes more damage than any other severe weather-related event, with an annual average cost of US $4.5 billion and an average of 17 fatalities per year between 1980 and 2024. FEMA’s outdated 100-year floodplain delineations fail to capture evolving flood risk, leading to development inside and outside of 100-year floodplains and potentially higher flood risk for vulnerable communities. Excluding development in 500-year floodplains would reduce risk, although encroachment of urban development into 500-year floodplains exacerbates risks. Despite extensive coastal flood risk and environmental justice research, few studies have been conducted in inland areas like the Intermountain West. Our study analyzes FEMA’s National Flood Hazard Layer and data from the 2017–2021 American Community Survey to quantify flood injustices in Salt Lake County, Utah. We develop a straight-forward and easily implementable approach for city and county level planning and flood injustice policymaking. Our objectives include assessing demographic attributes within and outside 500-year floodplains, identifying household and population flood injustices, and overlaying 500-year floodplain maps and selected flood injustice variables. Results show that although 44% of Salt Lake County’s 500-year floodplain is in the City of South Salt Lake, the cities of Millcreek and South Jordan emerge as most vulnerable for 500-year flood injustices, these cities have flood risk ratios of 1.92 and 1.67, respectively, where a risk ratio greater than 1.00 indicates potentially concerning flood injustice. These findings highlight observed inequities but do not indicate or prove systematic, intentional, or historical biases resulting from past or present discriminatory policies and practices within these cities. This study contributes to a deeper understanding of flood injustices in inland urban areas, shedding light on the intersection of flood risk and social vulnerability at microscales. Identifying flood injustice communities can inform targeted interventions and policy measures to mitigate flood injustices and enhance flood resilience and adaptation in inland urban areas for vulnerable communities.